Multidimensional Scaling Approach For Sustainable Tourism Development In Banyumas Regency - Damar Jati; Tri Esti Masita; Arkham Fadliansyah; Puji Rachmawati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study uses the Multi-Dimensional Scaling (MDS) method to analyze the sustainability status of five waterfall tourist destinations in Banyumas Regency and to guide future development strategies. This study is very important, given the limited research on the sustainability of Curug tourism, which faces challenges such as a declining number of visitors and a low economic contribution to Regional Original Revenue (PAD), at only 6.3%. Using five dimensions—Ecology, Economic, Socio-Cultural, Legal and Institutional, and Infrastructure and Technology—key findings show that overall sustainability status is in the "Moderately Sustainable" category. Curug Gede recorded the highest average score (54.59) and showed the best balance between the pillars, while Curug Ceheng was the only one categorized as "Less Sustainable" (44.746). Sustainability efforts are strongly supported by the Ecology and Legal and Institutional dimensions, but are consistently hampered by low scores on the economic and Socio-Cultural dimensions across locations. The leverage analysis highlights five attributes that are highly sensitive and require priority interventions: waste and emissions management (Ecology), tourism market potential (Economy), access for all (socio-cultural), implementation of natural resource surveillance (legal and institutional), and public transportation and technology-based promotion (infrastructure). These findings offer practical, long-term strategies to support holistic, sustainable development in the Curug tourism sector in Banyumas. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land